Elabela ameliorates doxorubicin-induced cardiotoxicity by promoting autophagic flux through TFEB pathway. (April 2022) - Chen, Deshu; Yu, Wenjie; Zhong, Chongbin; Hong, Qingqing; Huang, Guanlin; Que, Dongdong; Wang, Yuxi; Yang, Yashu; Rui, Bowen; Zhuang, Zhenyu; Liang, Miaoyuan; Ye, Zhicheng; et al.
Abstract: Doxorubicin (DOX) is a widely used and effective antineoplastic drug; however, its clinical application is limited by cardiotoxicity. A safe and effective strategy to prevent from doxorubicin-induced cardiotoxicity (DIC) is still beyond reach. Elabela (ELA), a new APJ ligand, has exerted cardioprotective effect against multiple cardiovascular diseases. Here, we asked whether ELA alleviates DIC. Mice were injected with DOX to established acute DIC. In vivo studies were assessed with echocardiography, serum cTnT and CK-MB, HW/BW ratio and WGA staining. Cell death and atrophy were measured by AM/PI staining and phalloidin staining respectively in vitro. Autophagic flux was monitored with Transmission electron microscopy in vivo, as well as LysoSensor and mRFP‐GFP‐LC3 puncta in vitro. Our results showed that ELA improved cardiac dysfunction in DIC mice. ELA administration also attenuated cell death and atrophy in DOX-challenged neonatal rat cardiomyocytes (NRCs). Additionally, we found that ELA restored DOX-induced autophagic flux blockage, which was evidenced by the reverse of p62 and LC3II, improvement of lysosome function and accelerated degradation of accumulated autolysosomes. Chloroquine, a classical autophagic flux inhibitor, blunted the improvement of ELA on cardiac dysfunction. At last, we revealed that ELA reversed DOX-induced downregulation of transcription factor EB (TFEB), and silencing TFEB by siRNA abrogated the effects of ELA on autophagic flux as well as cell death and atrophy in NRCs. In conclusion, this study indicated that ELA ameliorated DIC through enhancing autophagic flux via activating TFEB. ELA may become a potential target against DIC. Graphical Abstract: ga1